Potensi Ekstrak Daun Bandotan (Ageratum conyzoides L.) Sebagai Spray Untuk Pemulihan Luka Mencit Diabetik Yang Terinfeksi Staphylococcus aureus - Erra Ericha Safani; Wanodya Ayu Chandradevi Kunharjito; Alfiyan Lestari; Erlix Rakhmad Purnama (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2019)
Ageratum conyzoides L. leaf has the main compound of flavonoids and alkaloids that contribute to accelerate the healing process of diabetic ulcers with Staphylococcus aureus infection that can affect the quality of life of patients. This study aims to test the leaves of Ageratum conyzoides L. on the recovery of diabetic ulcers of mice infected with Staphylococcus aureus. The method used is the extraction of Ageratum conyzoides L leaves as the material of spray 15%, induction of diabetic compound (Alloxan monohydrate), length wound (1cm) and bacterial infections, and spray application with 1 times daily frequency, 2 times daily, 3 times a day for 9 days. The results showed that the lenght of wounds in group A, B, C, D, and E were 0,5; 0,8; 0,4; 0,2; 0,0. The administration of Ageratum conyzoides L. spray which has active flavonoide substances, alkaloid substance, and saponin substances has an effect on decreased length of diabetic wounds and restoration of dermis tissue structure (increases epithelial cells proliferation, initiates fibroblast cells, and stimulates type 1 collagen). Spray treatment 3 times a day (group E) was more influential than the other treatments, which experienced wound closure in 9 days. Thus, Ageratum conyzoides L. leaf spray is potential for therapy of diabetic ulcers infected with Staphylococcus aureus.